Cover Picture: Discovery of 5′′‐Chloro‐N‐[(5, 6‐dimethoxypyridin‐2‐yl)methyl]‐2, 2′:5′, 3′′‐terpyridine‐3′‐carboxamide (MK‐1064): A Selective Orexin 2 Receptor Antagonist (2‐SORA) for the Treatment of Insomnia (ChemMedChem 2/2014). Issue 2 (February 2014) - Roecker, Anthony J.; Mercer, Swati P.; Schreier, John D.; Cox, Christopher D.; Fraley, Mark E.; Steen, Justin T.; Lemaire, Wei; Bruno, Joseph G.; Harrell, C. Meacham; Garson, Susan L.; Gotter, Anthony L.; Fox, Steven V.; et al.
<x xml:space="preserve">Abstract</x> The front cover picture shows MK‐1064, a potent, orally bioavailable, selective orexin 2 receptor antagonist (2‐SORA) under evaluation as a potential treatment for insomnia. Orexin neuronal projections originating from the hypothalamus, shown in green, affect the activity of nuclei associated with arousal, vigilance state, and reward. Nuclei exhibiting preferential expression of orexin 1 receptor (OX1R), orexin 2 receptor (OX2R), and both OX1R and OX2R are shown in red, blue and violet, respectively. The lower left inlay depicts a homology model of OX2R bound by MK‐1064. The lower right inlay shows an orexin neuron secreting two peptide agonists, orexin‐A (OX‐A) and orexin‐B (OX‐B), and their binding to OX1R and OX2R. For more details regarding the discovery and development of MK‐1064, see the Full Paper by Anthony J. Roecker et al. on p. 311 ff. The homology modeling figure was provided by Dr. Kerim Babaoglu (Merck Chemistry Modeling and Informatics). Figure elements depicting the orexin neuron and receptor efferent pathways were taken from A. L. Gotter, A. L. Webber, P. J. Coleman, J. J. Renger, C. J. Winrow, Pharmacol. Rev. 2012, 64, 389–420 and reproduced with permission from the American Society of Pharmacology and Experimental Therapeutics. The cover art was produced in conjunction with Sharon O'Brien (Merck Creative Services).<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>